UV measurements at Marambio and Ushuaia during 2000–2010 ... : قياسات الأشعة فوق البنفسجية في مارامبيو وأوشوايا خلال الفترة 2000–2010 ... - Kaisa Lakkala; Alberto Redondas; Outi Meinander; Laura Thölix; Britta Hamari; Antonio Fernando Almansa; Virgilio Carreño; Rosa Delia García Cabrera; Carlos Torres; Guillermo Deferrari; Héctor A. Ochoa; Germar Bernhard; et al. (OpenAlex, 2018)
Abstract. Solar ultraviolet (UV) irradiances were measured with NILU-UV multichannel radiometers at Ushuaia (54∘ S) and Marambio (64∘ S) between 2000 and 2013. The measurements were part of the Antarctic NILU-UV network, which was started in cooperation between Spain, Argentina and Finland. The erythemally weighted UV irradiance time series of both stations were analysed for the first time. The quality assurance procedures included a travelling reference instrument to transfer the irradiance scale to the stations. The time series were homogenized and high quality measurements were available for the period 2000–2010. During this period UV indices of 11 or more were measured on 5 and 35 days at Marambio and Ushuaia, respectively. At Marambio, the peak daily maximum UV index of 12 and daily doses of around 7 kJ m−2 were measured in November 2007. The highest UV daily doses at both stations were typically around 6 kJ m−2 and occurred when the stations were inside the polar vortex, resulting in very low total ... : الملخص: تم قياس إشعاعات الأشعة فوق البنفسجية الشمسية باستخدام مقاييس الإشعاع متعددة القنوات NILU - UV في أوشوايا (54درجة مئوية) ومارامبيو (64درجة مئوية) بين عامي 2000 و 2013. كانت القياسات جزءًا من شبكة NILU - UV في أنتاركتيكا، والتي بدأت بالتعاون بين إسبانيا والأرجنتين وفنلندا. تم تحليل السلسلة الزمنية للأشعة فوق البنفسجية المرجحة حماميًا لكلا المحطتين لأول مرة. تضمنت إجراءات ضمان الجودة أداة مرجعية متنقلة لنقل مقياس الإشعاع إلى المحطات. كانت السلاسل الزمنية متجانسة وكانت القياسات عالية الجودة متاحة للفترة 2000–2010. خلال هذه الفترة، تم قياس مؤشرات الأشعة فوق البنفسجية البالغة 11 أو أكثر في 5 و 35 يومًا في مارامبيو وأوشوايا، على التوالي. في مارامبيو، تم قياس الحد الأقصى اليومي لمؤشر الأشعة فوق البنفسجية البالغ 12 والجرعات اليومية البالغة حوالي 7 كيلو جول متر مربع في نوفمبر 2007. كانت أعلى جرعات يومية من الأشعة فوق البنفسجية في كلتا المحطتين عادة حوالي 6 كيلو جول متر−2 وحدثت عندما كانت المحطات داخل الدوامة القطبية، مما أدى إلى انخفاض كبير في إجمالي كمية الأوزون. في كلتا المحطتين، يمكن أن تتجاوز الجرعات ...